2009
DOI: 10.1510/icvts.2008.201152
|View full text |Cite
|
Sign up to set email alerts
|

Surgical removal of an embolized patent ductus arteriosus coil from pulmonary artery without cardiopulmonary bypass

Abstract: We report the case of a 4-month-old girl who underwent patent ductus arteriosus (PDA) coil embolization. The coil had migrated into the left pulmonary artery and attempts to retrieve it with interventional techniques were unsuccessful. To prevent late effects of a foreign object in pulmonary artery, the patient was referred to surgery. The operation was done without cardiopulmonary bypass (CPB) and with the aid of a Fogarty catheter. Recovery was uneventful after the procedure. As far as we know this is the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…4 There have been many case reports regarding surgical treatment of an embolized device. [5][6][7] Although it is well defined in patients with atrial septal defect, percutaneous retrieval of an embolized device is rare in patients with patent ductus arteriosus. 8 In our case, we informed the patient of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…4 There have been many case reports regarding surgical treatment of an embolized device. [5][6][7] Although it is well defined in patients with atrial septal defect, percutaneous retrieval of an embolized device is rare in patients with patent ductus arteriosus. 8 In our case, we informed the patient of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate exposure during VATS or uncontrollable bleeding indicates conversion to thoracotomy. Rarely, urgent surgical management for embolized coils and occluder devices is needed …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, urgent surgical management for embolized coils and occluder devices is needed. 9 Various techniques for surgical correction of PDA were described. PDA was approached through thoracothomy or sternotomy, with or without the use of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…The device embolization can be seen in 0.55-3.8% of these cases. [2][3][4] However, this complication should be overcome primarily by percutaneous methods before an open surgical approach. Balbi et al [2] reported that the success rate of percutaneous retrieval of an embolized device is 50%.…”
mentioning
confidence: 99%
“…An embolized device may be simply rescued by using a loop snare, an endocardial biopsy forceps, a Fogarthy catheter, or a 15 mm Amplatz GooseNeck Snare, through a femoral arterial percutaneous access instead of this massive surgical operation. [3][4][5] In the light of all these aforementioned references, which are the obvious examples of how can an embolized device be rescued, the preference of a surgical option without trying any previous percutaneous maneuver seems to be incorrect.…”
mentioning
confidence: 99%